1996
DOI: 10.1002/(sici)1096-8628(19961211)66:2<209::aid-ajmg17>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

An autosomal dominant triphalangeal thumb: Polysyndactyly syndrome with variable expression in a large Indian family maps to 7q36

Abstract: Hereditary developmental abnormalities of the upper or lower limbs in humans are easily recognizable phenotypes that can be used in the mapping and cloning of genes involved in normal human development. We studied a large Indian pedigree (UR002) with an autosomal dominant triphalangeal thumb (TPT) and polysyndactyly (PSD). The abnormalities were present only in the upper limbs, and the phenotype was fully penetrant. The expression of the phenotype was variable and ranged from unilateral TPT to bilateral TPT, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…The human SHH gene is located in chromosome 7q36, the same region to which autosomal dominant (AD) sacral agenesis (OMIM 176450) and AD isolated triphalangeal thumb (OMIM 190605) have been linked (Heutink et al 1994;Tsukurov et al 1994;Hing et al 1995;Lynch et al 1995;Radhakrishna et al 1996). Using the same linkage markers as employed in the above-mentioned studies, we have shown that mirror polydactyly (OMIM 188770) is also linked to this region.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The human SHH gene is located in chromosome 7q36, the same region to which autosomal dominant (AD) sacral agenesis (OMIM 176450) and AD isolated triphalangeal thumb (OMIM 190605) have been linked (Heutink et al 1994;Tsukurov et al 1994;Hing et al 1995;Lynch et al 1995;Radhakrishna et al 1996). Using the same linkage markers as employed in the above-mentioned studies, we have shown that mirror polydactyly (OMIM 188770) is also linked to this region.…”
Section: Introductionmentioning
confidence: 73%
“…Penetrance seems to be complete or near complete (Canun et al 1984;Canun 1986). Family 9 (Radhakrishna et al 1996) is a multigenerational family presenting with isolated triphalangeal thumb. In family 11, tibial hemimelia and preaxial polydactyly of one foot are associated with findings of acromelic frontonasal dysplasia (Cunningham and Cloud 1997).…”
Section: Patients and Cell Linesmentioning
confidence: 99%
“…The majority of congenital limb abnormalities are polydactylies, with or without an associated malformation. Nevertheless, despite the complexity of classification, further molecular evidence indicated that some distinct phenotypic expressions of polydactylies might be allelic (5)(6)(7). Polydactylies are mainly classified as preaxial (PPD), mesoaxial, or post-axial (PAP), according to the axis information in most of these classifications (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…About 15 mouse preaxial polydactyly loci have been identified [Masuya et al, 1997], but only three have been mapped in humans: triphalangeal thumbpolysyndactyly on 7q36 [Heutink et al, 1994;Tsukurov et al, 1994;Hing et al, 1995;Radhakrishna et al, 1996]; Greig cephalopolysyndactyly due to a GLI3 mutation on 7p13 [Brueton et al, 1988]; and SALL1 mutation on 16q12.1 found in Townes-Brock syndrome [Kohlhase et al, 1998]. Most of the triphalangeal cases could be due to the 7q36 mutation since there is an extreme intrafamilial variability among the carriers of the same allele, but the responsible locus has not yet been identified.…”
Section: Discussionmentioning
confidence: 99%